2020
DOI: 10.3390/foods9050647
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hypertensive Activity of Novel Peptides Identified from Olive Flounder (Paralichthys olivaceus) Surimi

Abstract: There is a growing interest in the health benefits of functional foods. A benefit that has been long sought is the control of hypertension through dietary approaches. Hypertension has been implicated as a risk factor for cardiovascular disease and is therefore of clinical significance. Here, we aim to demonstrate the antihypertensive activity of novel peptides derived from surimi, a functional food ingredient made from refined fish myofibrillar proteins. Three peptides, Ile-Val-Asp-Arg (IVDR), Trp-Tyr-Lys (WYK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Therefore, the management and initial control of blood pressure (BP) could help minimize the risk of outbreak of hypertension. Recent research with animals revealed that marine fish hydrolysate and its bioactive peptide have strong angiotensin-I-converting enzyme (ACE) inhibitory activity in vitro and exponentially ameliorate blood pressure [9,[17][18][19][20]. However, most studies on marine fish hydrolysate have focused on their biological properties and adopted single-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the management and initial control of blood pressure (BP) could help minimize the risk of outbreak of hypertension. Recent research with animals revealed that marine fish hydrolysate and its bioactive peptide have strong angiotensin-I-converting enzyme (ACE) inhibitory activity in vitro and exponentially ameliorate blood pressure [9,[17][18][19][20]. However, most studies on marine fish hydrolysate have focused on their biological properties and adopted single-…”
Section: Discussionmentioning
confidence: 99%
“…Recent research with animals revealed that marine fish hydrolysate and its bioactive peptide have strong angiotensin-I-converting enzyme (ACE) inhibitory activity in vitro and exponentially ameliorate blood pressure [9,[17][18][19][20]. However, most studies on marine fish hydrolysate have focused on their biological properties and adopted single-enzyme-assisted hydrolysis to collect fish hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed several bioactive peptides which manage hypertension and cardiovascular disease through the interaction and regulation of eNOS and its associative kinases, probably showing better biosafety and bioavailability profile than standard small molecule drugs ( Cicero, Fogacci, & Colletti, 2017 ). A recent study conducted by Oh and colleagues investigated for bioactive peptides with antihypertensive and anti-inflammatory activities for from Olive flounder ( Paralichthys olivaceus ) ( Oh et al, 2020a , Oh et al, 2020b ) . Three bioactive peptides, VASVI, IVDR, WYK were found to significantly increase the level of nitric oxide in the HUVECs cell line.…”
Section: Recently Recognized Mechanisms Of Suppressing Blood Pressure...mentioning
confidence: 99%
“…Three bioactive peptides, VASVI, IVDR, WYK were found to significantly increase the level of nitric oxide in the HUVECs cell line. More so, there was a significant improvement in the expression of eNOS and protein kinase B (Akt) ( Oh et al, 2020a , Oh et al, 2020b ). Similarly, another study on Antarctic krill ( Euphausia superba) reported bioactive peptides (WF, YRK, and FQLFAS) with activities to improve the hypotensive marker– approximately 33% increase in NO and about 50 percent decrease in endothelin-1 (ET-1).…”
Section: Recently Recognized Mechanisms Of Suppressing Blood Pressure...mentioning
confidence: 99%
See 1 more Smart Citation